Hepatotoxic and neuroendocrine effects in physicians occupationally exposed to most modern halogenated anesthetics and nitrous oxide - Aun, Aline G. [UNESP] (2021)
The lack of data on hepatic and hormonal markers for occupational exposure to most modern halogenated anesthetics has stimulated our research, which assessed liver enzymes, high-sensitivity C-reactive protein (hs-CRP) and neuroendocrine response. The study investigated 106 physicians who were categorized in an exposed group (primarily exposed to isoflurane and sevoflurane and less to desflurane and nitrous oxide) as well as as a control group. Anesthetic air monitoring was performed, and biological samples were analyzed for the most important liver enzymes, hs-CRP, adrenocorticotrophic hormone, cortisol and prolactin. No biomarkers were significantly different between the groups. Exposed males showed significant increases in cortisol and prolactin compared to unexposed males. However, values were within the reference ranges, and 22 % of exposed males versus 5 % of unexposed males exhibited higher prolactin values above the reference range. This study suggests that occupational exposure to the most commonly used inhalational anesthetics is not associated with hepatotoxicity or neurohormonal changes.